PENGARUH MODEL PROJECT BASED LEARNING (PjBL) TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA SMP PADA MATERI PEMANASAN GLOBAL - Maulidia, Ananda Putri; Indrawati, Indrawati; Rusdianto, Rusdianto (Universitas Jember, 2023)
Creative thinking ability is crucial in the 21st century to prepare the creative, innovative, and contributing human resources in the community. However, the students' creative thinking ability is relatively low. This research's purpose is to study the effect of Project Based Learning model on junior high school student's creative thinking ability. This research is a quasi-experiment type with a non-equivalent control group design that is located in SMPN 1 Pakuniran on the 7th-grade students. Based on the analytic result, the normality test using Shapiro Wilk scored 0.259 for the experiment class and 0.64 for the control class (p value>0,05), the independent sample t-test scored 0,000 (sig.â‰¤0,05), and the right-tailed t-test scored 18,833 > 1,725. It can be concluded that Project Based Learning model has a significant effect on the creative thinking ability.